Seroepidemiological survey of Q fever in livestock and humans in Bura, Tana River County, Kenya - Mwololo, D.K. (University of Nairobi, 2016)
Q fever is a zoonotic disease caused by the intracellular bacterium Coxiella burnetii. It was first described in 1935. Ruminants are considered to be the primary source of infection to humans who become infected through inhalation of aerosols from infected ruminants and also through exposure to animal products such as unpasteurized dairy products. Clinical disease in animals is characterized by abortion and still births in sheep and goats while in cattle there is infertility and mastitis. In humans the disease syndrome can be divided into acute and chronic forms with the acute form manifesting as a relatively mild self-limiting febrile illness while the chronic form is a more severe disease characterized by hepatitis, pneumonia and chronic fatigue. This disease is therefore important due to its public health implications in humans and reproductive losses in animals. There are reports on the occurrence of this disease in Kenya, though very few studies have been published recently on the epidemiology of the disease and specifically in pastoral communities where livestock is the main source of livelihood. This study was therefore designed with the following objectives 1) To assess the knowledge, attitude and practices of the livestock owners in relation to Q fever and its control in Bura, Tana River County; 2) To estimate the seroprevalence of Q fever in livestock and humans in the study area; and 3) To determine the risk factors associated with the disease in livestock and humans. A seroepidemiological study was therefore carried out using an ELISA test to determine the occurrence of Coxiella burnetii antibodies in livestock (cattle sheep and goats) and humans in Bura, Tana River County. Questionnaires were also administered to household heads to determine the risk factors for Q fever. The prevalence of Coxiella burnetii antibodies in all animals surveyed was 13% (95% CI, 6.41-19.59%). The seroprevalence was higher in goats at 16% (95% CI, 8.81-23.19%) compared to sheep at 12% (95% CI, 5.63-18.37%) and cattle at 5.2 %, (95% CI, 0.85-9.55%). There were no statistically significant differences in the seroprevalence of Coxiella burnetii antibodies between animals sampled within the irrigation scheme versus those sampled within the manyattas at 12% (95% CI, 5.63-18.37%) and 14% (95% CI, 7.20-20.80%), respectively. Factors associated (P<0.05) with animal seropositivity were species, age and sex of the animal. Compared with adults, weaners were less likely to be seropositive (OR, 0.102; P= 0.002). With regard to species, goats were more likely to be seropositive compared to cattle (OR, 3.49; P=0.01). Two-hundred-and seventy-two humans were screened for antibodies against Coxiella burnetii. The seroprevalence of Coxiella burnetii was 26.8% (95% CI, 18.12-35.48%). The difference in the seroprevalence of Coxiella burnetii in individuals sampled within the irrigation scheme at 30.2% (95% CI, 21.20-39.20%), and those sampled in the non-irrigated areas at 16.4% (95% CI, 9.14-23.66%), was statistically significance. The seroprevalence for Coxiella burnetii among adults, children and adolescents was 34.2% (95% CI, 24.90-43.50%), 26.8% (95% CI, 18.12-35.48%) and 23.2% (95% CI, 14.93-31.47%), respectively. With regard to sex, there were slight differences in the seroprevalence of Coxiella burnetii among males and females occurring at 28% (95% CI, 19.20-36.80%) and 26% (95% CI, 17.40-34.60%) respectively. There were differences in the seroprevalence between different occupation groups with higher frequencies being reported amongst herdsmen and farmers at 42.9% (95% CI, 33.20- 52.60%) and 30.2% (95% CI, 21.20-39.20%), respectively. This difference was not significant. Sixteen percent (95% CI, 8.81-23.19%) and 11.8% (95% CI, 5.48-18.12%) of the individuals reported having experienced malaria and flu like symptoms within a period of two months before the study begun out of which 39.5% (95% CI, 29.92-49.08%) and 25% (95% CI, 16.51-33.49%) were seropositive for Coxiella burnetii antibodies, respectively. Risk factors associated (P<0.05) with individual and household seropositivity were occupation, irrigation status and animals housing within the family house (P<0.05). In the questionnaire survey, the respondents were neither aware of Q fever nor its risk factors. The only risk factor associated with Coxiella burnetii seropositivity was housing of animals within the family house whose odds were two times higher compared to households who did not house their animals within their living house. The present study confirmed the occurrence of Coxiella burnetii in the study area. The high prevalences in both the livestock and humans sampled may have been due to the low levels of awareness on this condition and the subsequent lack of control measures. Land use change to irrigation may also have increased the risk of infection especially in the human population. It is therefore necessary to employ appropriate strategies for diagnosis of Q- fever patients by equipping local and national laboratories and increasing the knowledge of physicians of potential clinical signs of the disease and how to make a diagnosis of the same. Community education and awareness creation would also be very helpful in preventing Q -fever infection. There is therefore need for the government to have control strategies for the disease such as introduction of vaccination which is currently not being carried out in the country. Further research to determine the effect of land use change on tick-borne diseases in Kenya should also be carried out.